Analysis of Students’s Mathematical Communication Ability in Learning Mathematics Using the Jigsaw Cooperative Method - Wulandari, Firnanda Safira; Cholily, Yus Mochamad; Kusumawardhana, Adi Slamet (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
This research aims to determine students' mathematical communication skills in mathematics which was carried out using the Jigsaw cooperative method. The research method uses experimental research. The design in this research leads to a true experimental design with a posttest-only control design. The sampling technique was simple random sampling taken from odd semester student report cards. The research sample consisted of 2 classes, namely class VIIA and VIIB. The research instrument consists of a test sheet consisting of five descriptive questions with material about plane figures and an observation sheet containing two indicators of mathematical communication, written and oral. The data analysis technique uses an independent T-Test, so it can be concluded that (1) the Jigsaw type cooperative learning method has an effect on students' mathematical communication skills. (2) Independent sample T-Test with a significance value of  showing a significant difference between class VII A as the experimental class and class VIIB as the control class.